L’incubation et l’éclosion des oeufs des vers à soie de chêne Antheraea pernyi Guer (Bombycidae) - Nueleanu, Veturia - Ileana (Acta Agraria Debreceniensis, 2003)
In this paper we studied optimal conditions which need to be fulfilled in order to have successful incubation and hatching of eggs of the species Antheraea pernyi Guer.The incubation of the eggs of this species implies a proper environment: temperature of 18-21oC, relative humidity of 80%, unvarying light, aeration 2 or 3 times a day and a density of 50 g eggs for a 20/50 cm area.In these conditions, the incubation of the first generation lasts 10-12 days and of the second generation up to 8-10 days. The second generation needs higher temperatures (22-26oC) and higher humidity (optimal value 90%).In this species, hatching lasts 6-7 days, with a maximum during the second day; it takes place especially early in the morning.